2005
DOI: 10.1016/j.bbrc.2005.05.191
|View full text |Cite
|
Sign up to set email alerts
|

Saururus cernuus lignans—Potent small molecule inhibitors of hypoxia-inducible factor-1

Abstract: Hypoxia-inducible factor-1 (HIF-1) represents an important tumor-selective therapeutic target for solid tumors. In search of novel small molecule HIF-1 inhibitors, 5400 natural product-rich extracts from plants, marine organisms, and microbes were examined for HIF-1 inhibitory activities using a cell-based reporter assay. Bioassay-guided fractionation and isolation, followed by structure elucidation, yielded three potent natural product-derived HIF-1 inhibitors and two structurally related inactive compounds. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
88
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(90 citation statements)
references
References 41 publications
2
88
0
Order By: Relevance
“…The 13 C NMR spectrum (Table 2) contained 30 carbon resonances, and the 13 C DEPT spectrum indicated the presence of seven methyl groups, eleven methylenes, five methines and seven quaternary carbon atoms. 15 Comparison of the 13 C NMR spectroscopic data of 1 with those of sodwanone K, showed nearly complete analogy of the chemical shifts, except for C-2 and C-3. Clear NOESY correlations between H-24 and H-7; and between H-25 and H-26 suggested that the relative configuration of this portion of 1 was similar to that of sodwanone K, except that a NOE between H-3 and H-24 indicated that 1 was the C-3 epimer of sodwanone K. The absolute configuration of C-3 was determined using the modified Mosher ester method.…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…The 13 C NMR spectrum (Table 2) contained 30 carbon resonances, and the 13 C DEPT spectrum indicated the presence of seven methyl groups, eleven methylenes, five methines and seven quaternary carbon atoms. 15 Comparison of the 13 C NMR spectroscopic data of 1 with those of sodwanone K, showed nearly complete analogy of the chemical shifts, except for C-2 and C-3. Clear NOESY correlations between H-24 and H-7; and between H-25 and H-26 suggested that the relative configuration of this portion of 1 was similar to that of sodwanone K, except that a NOE between H-3 and H-24 indicated that 1 was the C-3 epimer of sodwanone K. The absolute configuration of C-3 was determined using the modified Mosher ester method.…”
Section: Resultsmentioning
confidence: 93%
“…Comparison of the 1 H and 13 C NMR spectra of 7 (Tables 1 and 2) with those of 4 indicated that the bicyclic C-2-C-11 portion of the structures were analogous in both compounds. Long-range 1 H- 13 Thus 7 possess a new carbon skeleton where the two separate bicyclic portions of the structure are connected at the bridgehead carbon C-19 by the C-12 -C-13 linker. This new sodwanone analog was assigned the trivial name sodwanone U (7).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations